Scenario-guided participatory enhancement of Costa Rica’s Nationally Determined Contribution - Veeger, Marieke (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Countries need to enhance the ambition of their Nationally Determined Contributions (NDCs) in order to prevent catastrophic effects of temperature increase over 2 degrees Celsius. More frequent and severe weather events across the globe have shown us the urgency of this matter. To limit global warming to 1.5 degrees Celsius, economies will need to go through deep transformations. However, planning for societal changes of this magnitude is complex, and major uncertainty about future developments can hold countries back from setting ambitious goals. NDC enhancement processes, which should take place at least every five years, need to include segments where stakeholders of different backgrounds and sectors collectively imagine how those transformations could take place, and what could make or break the transcendental emission reduction and climate change resilience that is needed. In this Info Note we exemplify how this can be done by mapping out how Costa Rica used a highly participatory approach to anticipate possible futures, increase ambitions and robust climate action, resulting in an NDC with enhanced climate ambitions.